Analysis of the Factors That Influence the Decision of Cayenne Pepper Farmers to Adopt Organic Fertilizer in Bone Raya District - Tilohe, Maiqshal; Moonti, Agustinus; Machieu, Siti Rahmatia (Majapahit Journal of Islamic Finance and Management, 2025)
The challenge faced by cayenne pepper farmers in Indonesia, especially in poor rural areas, is their high dependence on subsidized chemical fertilizers. One solution introduced through counseling to farmers on the use of organic fertilizers by cayenne pepper farmers, the purpose of this study is to (1) determine the characteristics of organic fertilizer adoption in Bone Raya District and (2) determine the factors that influence organic fertilizer adoption in Bone Raya District. This study was conducted in Bone Raya District, Bone Bolango Regency, Gorontalo Province using a quantitative approach with descriptive analysis research essays used in this study, with a total of 50 cayenne pepper farmers in Bone Raya District as respondents. These results indicate that the level of organic fertilizer adoption by cayenne pepper farmers is less than optimal. This can be seen from the 40% of the total cayenne pepper land in Bone Raya District that applies organic fertilizer.